Rondostreptus, a new spirostreptid genus from southeastern Tanzania (Diplopoda: Spirostreptidae) - Hoffman, Richard L. (Zootaxa, 2011)
The name Rondostreptus kiellandi is proposed for an undescribed genus and species of Spirostreptidae apparently endemic to the Rondo Plateau in southeastern Tanzania. It appears to have no close relatives among the known spirostreptid fauna of East Africa.